On the physical basis of a Larson-Miller constant of 20. (January 2018) - Maruyama, K.; Abe, F.; Sato, H.; Shimojo, J.; Sekido, N.; Yoshimi, K.
Abstract: Larson-Miller (LM) and Orr-Sherby-Dorn (OSD) parameters are widely used when formulating and predicting creep rupture life t r . The LM constant C and the activation energy Q in the OSD parameter characterize temperature dependence of t r . Q = Q LSD ( Q LSD : activation energy for lattice self-diffusion) and C = 20 are often assumed in the formulation. Creep rupture datasets of 11 heats of nickel alloy A617, 304H and 304J1 stainless steels, 6 heats of A3004N aluminum alloy and four Mg-Al alloys are formulated with the parameters for determining C and Q of each dataset. Based on the correlation between C and Q among similar materials, it is discussed what is the C value equivalent to Q = Q LSD . It is also examined how the C value changes with melting temperature of the material. The value of C equivalent to Q = Q LSD varies from 14 to 9.5 depending on average values of log(rupture life) and of reciprocal temperature of the dataset. These values of C point out that C = 20 is not equivalent to Q = Q LSD . The equivalent C values are similar in all the materials independently of their melting temperatures. Highlights: Larson-Miller constant C is correlated to Orr-Sherby-Dorn constant Q by an equation. C takes about 12 when Q is equal to activation energy for lattice diffusion. C is proved to be insensitive to melting temperature of the material. Q decreases to activation energy for lattice diffusion in long-term creep.